2015
DOI: 10.18632/oncotarget.4927
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1 regulates androgen receptor variant activity in models of castrate-resistant prostate cancer

Abstract: Retention of androgen receptor (AR) signalling in castrate-resistant prostate cancer (CRPC) highlights the requirement for the development of more effective AR targeting therapies. A key mechanism of resistance to anti-androgens is through expression of constitutively active AR variants (AR-Vs) that are refractory to next-generation therapies, including Enzalutamide and Abiraterone. By maintaining an androgenic gene signature, AR-Vs drive tumour survival and progression in castrate conditions. Critically, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 45 publications
(77 reference statements)
11
41
0
Order By: Relevance
“…1) based on sequence similarity within and outside of the forkhead box (Hannenhalli and Kaestner, 2009;Kaestner et al, 1999). In many cases, the homozygous deletion of just one Fox gene leads to embryonic or perinatal lethality and, in humans, mutations in or the abnormal regulation of Fox genes are associated with developmental disorders and diseases such as cancer Li et al, 2015a;Wang et al, 2014b;Zhu et al, 2015;DeGraff et al, 2014;Halmos et al, 2004;Ren et al, 2015;Jones et al, 2015;Habashy et al, 2008), Parkinson's disease (Kittappa et al, 2007), autism spectrum disorder (Bowers and Konopka, 2012), ocular abnormalities (Acharya et al, 2011), defects in immune regulation and function (Mercer and Unutmaz, 2009) and deficiencies in language acquisition (Takahashi et al, 2009); see Table 1 for a comprehensive overview of Fox transcription factor expression patterns and their association with developmental disorders and disease.…”
Section: An Overview Of Fox Transcription Factorsmentioning
confidence: 99%
“…1) based on sequence similarity within and outside of the forkhead box (Hannenhalli and Kaestner, 2009;Kaestner et al, 1999). In many cases, the homozygous deletion of just one Fox gene leads to embryonic or perinatal lethality and, in humans, mutations in or the abnormal regulation of Fox genes are associated with developmental disorders and diseases such as cancer Li et al, 2015a;Wang et al, 2014b;Zhu et al, 2015;DeGraff et al, 2014;Halmos et al, 2004;Ren et al, 2015;Jones et al, 2015;Habashy et al, 2008), Parkinson's disease (Kittappa et al, 2007), autism spectrum disorder (Bowers and Konopka, 2012), ocular abnormalities (Acharya et al, 2011), defects in immune regulation and function (Mercer and Unutmaz, 2009) and deficiencies in language acquisition (Takahashi et al, 2009); see Table 1 for a comprehensive overview of Fox transcription factor expression patterns and their association with developmental disorders and disease.…”
Section: An Overview Of Fox Transcription Factorsmentioning
confidence: 99%
“…The mechanism of action has been elucidated, with the chromatin remodelling enzyme LSD1 being recruited by ARE-bound activated AR resulting in histone H3K4me1,2 demethylation and subsequent downregulation (Cai et al 2014). A role for the pioneer transcription factor FOXA1, in this negative regulation, has also been identified (Jones et al 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…A recent study suggested that NONOG, a pluripotency transcription factor, reprograms prostatic cancers to become castration resistant by dynamically repressing and engaging the AR/FOXA1 signaling axis [121]. Another recent study suggests that AR variants are dependent on FOXA1 for sustaining a pro-proliferative gene signatures and agents targeting FOXA1 may represent novel therapeutic options for patients with castrate-resistant prostatic cancer [122]. …”
Section: Molecular Characteristics Of Prostatic Cancermentioning
confidence: 99%